1996
DOI: 10.1071/rd9960931
|View full text |Cite
|
Sign up to set email alerts
|

Localization by indirect immunofluorescence of nitric oxide synthase in mouse and human spermatozoa

Abstract: The localization of nitric oxide synthase was studied in mouse epididymal spermatozoa and freshly ejaculated human sperm. A rabbit antiserum against the neuronal isoform of the enzyme was used, and antibody binding was detected with a fluorescein isothiocyanate-conjugated polyclonal antibody specific for rabbit IgG. In mouse spermatozoa, the percentage of cells staining specifically ranged from 88% to 98%. Samples were examined after 0-, 90- and 150-min incubations in vitro. Three different patterns of stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 0 publications
9
56
0
1
Order By: Relevance
“…In epididymal mouse sperm loaded with 4-amino-5-methylamino-2 0 ,7 0 -difluorofluorescein diacetate (DAF-FM DA) the distribution of NO changed from the head and midpiece to the midpiece upon capacitation (Fig. 4A, upper panels a and c), consistent with previously reported NOS relocalization (Herrero et al 1996).…”
Section: Gst-spink3 Treatment Correlates With Reduced No Production Isupporting
confidence: 79%
See 1 more Smart Citation
“…In epididymal mouse sperm loaded with 4-amino-5-methylamino-2 0 ,7 0 -difluorofluorescein diacetate (DAF-FM DA) the distribution of NO changed from the head and midpiece to the midpiece upon capacitation (Fig. 4A, upper panels a and c), consistent with previously reported NOS relocalization (Herrero et al 1996).…”
Section: Gst-spink3 Treatment Correlates With Reduced No Production Isupporting
confidence: 79%
“…SPINK3 involves NO signalling in sperm immunofluorescence using antibodies that cannot distinguish among NOS forms (Herrero et al 1996). However, de Lamirande & Lamothe (2009) observed, using the same probe, an increase of NO signal on the head in human sperm during capacitation.…”
mentioning
confidence: 99%
“…In the present study, the pre-and post-bleaching images for the FRET data revealed the close interaction of PMCA4 and the NOSs on the sperm head, neck (Figures 2 and 3), and on the proximal principal piece of the flagellum, reflecting their co-localization. This is the first report of the localization for eNOS in murine sperm (Figures 1a and 3) and our results provide confirmation of that reported for nNOS by Herrero et al (1996). These localizations in murine sperm are similar to what has been reported for nNOS and eNOS in human sperm (Andrews et al, 2015;Herrero et al, 1996; O'Bryan, Zini, Cheng, & Schlegel, 1998), where they were also shown to co-localize (Andrews et al, 2015).…”
Section: Resultssupporting
confidence: 79%
“…Thus, when WT and nulls were compared, UNCAP and CAP, the median fluorescence units for each increased ∼2-fold for nulls versus WT-sperm (Figure 5a,b). 4 | DISCUSSION 4.1 | PMCA4 and the NOSs co-localize and intimately interact in murine sperm in a Ca 2+ -dependent manner While PMCA4 (Aravindan et al, 2012;Wennemuth et al, 2003) and nNOS (Herrero, Perez Martinez, Viggiano, Polak, & Gimeno, 1996) have been localized in murine sperm on the head, over the acrosome, Figure 1a, we show that nNOS is more abundant and more widely distributed on the sperm, being found in the distal principal piece where eNOS and PMCA4 do not reside. In the present study, the pre-and post-bleaching images for the FRET data revealed the close interaction of PMCA4 and the NOSs on the sperm head, neck (Figures 2 and 3), and on the proximal principal piece of the flagellum, reflecting their co-localization.…”
Section: Resultsmentioning
confidence: 81%
“…NO has been demonstrated to play a role in a variety of functions in the human reproductive tract, including sperm motility (Lewis et al 1996), chemotaxis (Miraglia et al 2007), and sperm-zona pellucida binding ability (Sengoku et al 1998). NOS isoforms have been localized in the acrosome and tail of human, mouse, and bovine spermatozoa (Herrero et al 1996, Meiser & Schulz 2003, and low motility spermatozoa have been shown to exhibit aberrant patterns of NOS3 immunostaining (O'Bryan et al 1998). It has been reported that low concentrations of NO (25-100 nM sodium nitroprusside) enhance the motility of human spermatozoa (Hellstrom et al 1994, Zhang & Zheng 1996.…”
Section: Introductionmentioning
confidence: 99%